Investigating Buying-Selling Communication Patterns in The Kangean Community at Kalikatak Market: An Ethnographic Communication Approach - Mohamad Sudi,; Hanif Saputra Affandi,; Damayanti Masduki,; Siska Armawati Sufa,; Lela Susanty , (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This research aims to investigate the communication dynamics within the Kangean community during buying and selling activities at Kalikatak Market, employing an ethnographic communication approach. Through participant observation and interviews, the study explores communication strategies, language variations, linguistic codes, and cultural norms prevalent in these interactions. Data collection involved attentive listening, recording, and note-taking during market interactions, supplemented by a reflective introspective method to engage both researcher and respondents in communication patterns. The speech data collected was transcribed, condensed, categorized, and validated, leading to the interpretation of findings represented in a visual scheme illustrating communication dynamics. The study reveals the predominant use of the Kangean Dialect Malay Language (KDML) with the ako-kao language variety in buying and selling interactions, along with the role of non-verbal cues as signals and linguistic codes reflecting cultural identity. Additionally, cultural norms emphasizing sincerity, attentiveness, and honesty were observed. This research provides valuable insights into the communication patterns within the Kangean community at Kalikatak Market, shedding light on the intricacies of social interaction in a marketplace setting and suggesting avenues for further exploration.